Protein mediated synthesis of Au-Ag bimetallic nanoparticles - Raju, D.; Mendapara, Ritul; Mehta, Urmil J. (Materials Letters, 2014)
There is growing need to develop environment friendly method for synthesis of bimetallic nanoparticle that do not use toxic chemicals during their synthesis process. Here, we report synthesis of Au-Ag bimetallic nanoparticles by using macerase enzyme as reducing agent at different temperatures. Bimetallic nanoparticles were synthesized at 80 and 90 degrees C. The intensity of formation of nanoparticles was more at 80 degrees C. The bimetallic nanoparticles are characterized by using UV-vis, TEM and EDAX. The TEM study shows the inner gold and outer silver bimetallic nanoparticles. The formed nanoparticles are 4-20 nm in size and spherical in shape. EDAX confirms the formed bimetallic nanoparticles are of gold and silver. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Enzyme; Gold; Macerase; Particles; Silver; synthesis